Implementation of assessment standards in improving the quality of public elementary schools in Tempting subdistrict, Indragiri Hilir regency - Suryadi; Isjoni; Bunari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The research focuses on implementing educators' assessment standards per Minister of Education and Culture Regulation Number 23 of 2016 at State Elementary Schools in Tempuling District, Indragiri Hilir Regency. The approach used in this research is a qualitative descriptive approach. Through this descriptive method, researchers hope to see the phenomena in connection with implementing assessment standards in State Elementary Schools in Tempuling District, Indragiri Hilir Regency. The research was carried out at the Tempuling District Public Elementary School, Indragiri Hilir Regency, which consists of three state schools. The research period is from January to August 2023. Data collection techniques used document review, observation, and interview methods. The analysis technique uses three channels, namely: (a) data reduction, (b) data presentation, and (c) conclusion. Based on the research and discussion above, it can be concluded that educators have not fully mastered the concept of learning assessment.